Comparison of morphological variations among three species of the genus Paracobitis in Iran using geometric morphometrics method with a taxonomical review on the genus in Iran - Omid Jafari; Soheil Eagderi; Maryam Nasrolah-Pourmoghadam; Hashem Noferesti; Hamed Mosavi-Sabet (تاکسونومی و بیوسیستماتیک, 2015)
This study was conducted to apply the landmark-based geometric morphometrics technique to differentiate three species of the genus Paracobitis (P. iranica, P. malapterura and P. rhadinaeus) in Iran based on their body shape, because previous works, using traditional morphometrics, could not distinct them. A total of 150 specimens were sampled from the Zaringol, Madarsoo, Ghomrood, Kordan Rivers and Chahnimeh reservoir. The left side of the specimens was photographed using a digital camera and then fifteen landmark-points were digitized on two-dimensional images using TpsDig2. Landmark data were analyzed after a generalised procrustes analysis using PCA, CVA and cluster analysis. The patterns of body shape differences among the populations were illustrated in the deformation grids in relation to consensus configuration. The results showed a significant differences among the studied species and their populations in terms of morphological traits (P<0.0001). Some differences were found in the length and depth of head, depth of body, caudal peduncle length and position of eye and position of dorsal fin. The result also showed that P. iranica from Kordan River can be considered to be a distinct taxon compared to the Ghomrood taxon based on its morphological characteristics. In addition, our findings revealed that the geometric morphometrics approach can be a proper tool for morphological and taxonomic studies in species with small sizes including Nemachelinae.